Personal Neoantigens From Patients With NSCLC Induce Efficient Antitumor Responses - Zhang, Wei; Yin, Qi; Huang, Haidong; Lu, Jingjing; Qin, Hao; Chen, Si; Zhang, Wenjun; Su, Xiaoping; Sun, Weihong; Dong, Yuchao; Li, Qiang (Frontiers in Oncology, 2021)
Objective: To develop a neoantigen-targeted personalized cancer treatment for non-small cell lung cancer (NSCLC), neoantigens were obtained from collected human lung cancer samples, and the utility of neoantigen and neoantigen-reactive T cells (NRTs)was assessed. Methods: Tumor specimens from three patients with NSCLC were obtained and analyzed by whole-exome sequencing, and neoantigens were predicted accordingly. Dendritic cells and T lymphocytes were isolated, NRTs were elicited and IFN-γ ELISPOT tests were conducted. HLA-A2.1/Kb transgenic mice were immunized with peptides from HLA-A*02:01+ patient with high immunogenicity, and NRTs were subjected to IFN-γ, IL-2 and TNF-α ELISPOT as well as time-resolved fluorescence assay for cytotoxicity assays to verify the immunogenicity in vitro. The HLA-A*02:01+ lung cancer cell line was transfected with minigene and inoculated into the flanks of C57BL/6nu/nu mice and the NRTs induced by the immunogenic polypeptides from autologous HLA-A2.1/Kb transgenic mice were adoptively transfused to verify their immunogenicity in vivo. Results: Multiple putative mutation-associated neoantigens with strong affinity for HLA were selected from each patient. Immunogenic neoantigen were identified in all three NSCLC patients, the potency of ACAD8-T105I, BCAR1-G23V and PLCG1-M425L as effective neoantigen to active T cells in suppressing tumor growth was further proven both in vitro and in vivo using HLA-A2.1/Kb transgenic mice and tumor-bearing mouse models. Conclusion: Neoantigens with strong immunogenicity can be screened from NSCLC patients through the whole-exome sequencing of patient specimens and machine-learning-based neoantigen predictions. NRTs shown efficient antitumor responses in transgenic mice and tumor-bearing mouse models. Our results indicate that the development of neoantigen-based personalized immunotherapies in NSCLC is possible. Precis: Neoantigens with strong immunogenicity were screened from NSCLC patients. This research provides evidence showing that neoantigen-based therapy might serve as feasible treatment for NSCLC.